The collapse of the material foundations of Westphalian International Law - Diniz, Eugenio; Proença Júnior, Domício (Revista de Sociologia e Política, 2015)
This article corresponds to a diagnosis that affirms the collapse of the material foundations of coercive power, the hard constraints of any political direction that seeks to reform of international regulation. It takes the matter within the broad parameters associated with International Law derived from the Treaty of Westphalia, including some of its developments. The evolution of International Law is addressed through the perspective of Strategic Studies to show how the Westphalian order was consistent with then-current underlining strategic, tactical and logistical realities, and then proceeds to demonstrate how those underlining realities have changed. The contrast between current International Law and current strategic, tactical and logistical realities exposes the former as fundamentally at odds, with the latter, which is an untenable situation. Failure to directly address those inconsistencies in an intellectually sustained effort tends to perpetuate a state of affairs in which International Law will be redefined exclusively by the decisions of the powerful and the arbitrary rule of the stronger.